2016
DOI: 10.4328/jcam.2907
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptom Prevalence and Risk Factors in Eastern Turkish University Students

Abstract: Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Mental health problems among university students are an emergent public health issue and evidencebased prevention is crucial (Dahlin et al, 2011) and it is particularly predominant in higher education (Yusoff et al, 2013;Hubble and Bolton, 2020). Studies also have shown that the number of depression and anxiety cases has been increasing among university students in recent years (Arslan et al, 2009;Kıvrak et al, 2016), with evidence that these levels are inversely related to students' life quality (Oztasan et al, 2016). According to the Institute for Public Policy Research (IPPR) report, in 2015/16, 15, 395 UK-domiciled first-year university students disclosed a mental health condition-almost five times the number ten years ago (Thorley, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health problems among university students are an emergent public health issue and evidencebased prevention is crucial (Dahlin et al, 2011) and it is particularly predominant in higher education (Yusoff et al, 2013;Hubble and Bolton, 2020). Studies also have shown that the number of depression and anxiety cases has been increasing among university students in recent years (Arslan et al, 2009;Kıvrak et al, 2016), with evidence that these levels are inversely related to students' life quality (Oztasan et al, 2016). According to the Institute for Public Policy Research (IPPR) report, in 2015/16, 15, 395 UK-domiciled first-year university students disclosed a mental health condition-almost five times the number ten years ago (Thorley, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a syndrome with symptoms such as constant sadness, stagnation, unwillingness, feeling of worthlessness, sadness, inadequacy, pessimism, and physiological slowdown in functioning (Goodwin, 2006). It is expressed as a social health problem in that it becomes chronic in individuals and has a high probability of recurrence (Kivrak et al, 2016). Therefore, it is thought that some measures should be taken in order to minimize the negative effects of depression and to prevent especially healthy individuals from falling into depression.…”
Section: Introductionmentioning
confidence: 99%